Pneumocystis jirovecii Pneumonia in Pediatric Inflammatory Bowel Disease: A Case Report and Literature Review - Lawrence, Sally J.; Sadarangani, Manish; Jacobson, Kevan (Frontiers in Pediatrics, 2017)
Immunosuppressive therapy is a known risk factor for opportunistic infections. We report the first case of severe Pneumocystis jirovecii infection requiring intensive care in a pediatric patient with inflammatory bowel disease (IBD). The literature was reviewed and there were 92 reported cases of pneumocystis pneumonia (PCP) in patients with IBD. Most sources were case reports and there was likely reporting bias towards patients receiving immunomodulators, anti-tumor necrosis factor (anti-TNF) therapy and those who died. Overall, 56% of patients were male and 58% had crohn’s disease (CD). The median age was 45 years (interquartile range 30-68, range 8-78) and 86% of patients were lymphopenic. The case-fatality rate was 23%. Corticosteroids were used as IBD treatment in 88% of patients who subsequently developed PCP, 42% received thiopurines, 44% used anti-TNF therapy and 15% received either ciclosporin or tacrolimus. Rates of mono, dual, triple and quadruple immunosuppression therapy were 35%, 35%, 29% and 2% respectively. This report highlights the importance of considering PCP in immunosuppressed lymphopenic pediatric IBD patients who present with unusual symptoms. Moreover, it should give gastroenterologists the impetus to limit immunosuppressive therapy to its minimal effective dose and consider options such as exclusive enteral nutrition (EEN) wherever possible. Although there is no place for global PCP prophylaxis in IBD given the low incidence, in an era when there is increasing use of biologic agents with combination immunosuppressive therapy, the risk-benefit profile of PCP chemoprophylaxis should be revisited in selected cohorts such as patients on triple immunosuppression with corticosteroids, thiopurines and a biological agent or calcineurin inhibitor, especially in lymphopenic individuals.